New aspects on canine spirocercosis - MYLONAKIS (Μ.Ε. ΜΥΛΩΝΑΚΗΣ) M. E.; KOUTINAS (Α.Φ. ΚΟΥΤΙΝΑΣ) A. F.; RALLIS (Τ. ΡΑΛΛΗΣ) T. (Journal of the Hellenic Veterinary Medical Society, 2017)
Spirocerca lupi is a nematode parasite of carnivores affecting mainly the dog. Although S. lupi infection is often asymptomatic, esophageal granulomas and/or sarcomas, aortic aneurysms, thoracic discospondylitis or spondylosis deformans, hypertrophic osteopathy and salivary gland necrosis may be detected in various combinations upon the necropsy of dogs, originating from the endemic areas. When spirocercosis turns symptomatic, regurgitation, vomiting, odynophagia, hypersalivation, progressive loss of body weight, dyspnea and episodic melena are the most common clinical signs noticed. Diagnosis will be confirmed by fecal examination (egg detection), using flotation or sedimentation techniques, thoracic radiography (posterior mediestinal mass, vertebral lesions) and especially esophagoscopy, which allows the direct visualization of S. lupi nodules either granulomatous or neoplastic. Avermectins, such as doramectin and ivermectin, have been emerged as promising medications in the treatment and possibly in the prevention of canine spirocercosis. Their use, in both the spontaneous and experimental disease, has resulted in the remission of esophageal dysphagia, complete or partial regression of esophageal parasitic granulomas and cessation of egg shedding.